AUGMENTED REALITY AND MODERN SPORT MANAGEMENT - Sriburi, Suttinee (Journal of Modern Sport Management, 2022)
This article aims to present a concept of applying the Augmented Reality (AR) technology in sport management by synthesizing, analyzing, and summarizing previous related articles and researches. The results showed that the benefits of AR technology used in sport sectors are the developing athletes’ performance, assisting referees’ decision, improving marketing strategies and enhancing sport broadcasting experience. However, there are obstacles including high cost of software investment, lack of AR technology implementation, limitation of instruments and internet network, applying AR technology in sport management seems ineffectiveness. Therefore, it can be concluded that AR technology will plays an important role in developing both sport science and sport industry sectors directly nor indirectly. Even though, there are a lot of benefits of applying AR in sport management, the obstacles cannot be neglect. In-deep research and teamworking have to be done as well as surveying the users’ opinion and satisfaction for designing and developing the system to maximize the results and fit to the application of every purposes.